Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1002/mas.10061
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray mass spectrometry of phospholipids

Abstract: Phospholipids play a central role in the biochemistry of all living cells. These molecules constitute the lipid bilayer defining the outer confines of a cell, but also serve as the structural entities which confine subcellular components. Mass spectrometry has emerged as a powerful tool useful for the qualitative and quantitative analysis of complex phospholipids, including glycerophospholipids and the sphingolipid, sphingomyelin. Collision induced decomposition of both positive and negative molecular ion spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
769
2
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 847 publications
(796 citation statements)
references
References 106 publications
19
769
2
6
Order By: Relevance
“…One way to achieve detailed structural analysis of glycerophospholipids is by using electrospray tandem mass spectrometry [8]. Glycerophospholipids consist of a glycerol backbone with a fatty acyl or 1-O-alkyl group at the sn-1 position, an acyl group at the sn-2 position, and a phosphate ester group with a polar head group at the sn-3 position.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One way to achieve detailed structural analysis of glycerophospholipids is by using electrospray tandem mass spectrometry [8]. Glycerophospholipids consist of a glycerol backbone with a fatty acyl or 1-O-alkyl group at the sn-1 position, an acyl group at the sn-2 position, and a phosphate ester group with a polar head group at the sn-3 position.…”
mentioning
confidence: 99%
“…Glycerophospholipids consist of a glycerol backbone with a fatty acyl or 1-O-alkyl group at the sn-1 position, an acyl group at the sn-2 position, and a phosphate ester group with a polar head group at the sn-3 position. Collision-induced dissociation of the [M ϩ H] ϩ or [M Ϫ H] Ϫ of glycerophospholipids results in fragment ions that are related to the polar head group and the fatty acyl substituents esterified to the glycerol backbone [8]. One of the principal fragmentation pathways during collision-induced dissociation (CID) in the positive ion mode is cleavage of the phosphate-glycerol bond, which results in the elimination of the polar head group as a neutral or charged species.…”
mentioning
confidence: 99%
“…A number of studies have demonstrated the use of mass spectrometry for characterization of phospholipids and particularly cardiolipin (for review, see [13]). Most recently, for example, Hsu and Turk [14] described a multiple-stage ion-trap mass spectrometric approach with electrospray ionization for structural characterization of cardiolipin.…”
mentioning
confidence: 99%
“…However, there are many disadvantages to using TLC for phospholipid analysis. First, the technique may destroy the phospholipid structure (Pulfer and Murphy, 2003) owing to either oxidation or hydrolysis of the phospholipids while exposed to the atmosphere on the plate (Guan et al, 2001). Second, TLC has relatively poor reproducibility compared with HPLC or GC (Breton et al, 1989).…”
Section: Thin-layer Chromatographymentioning
confidence: 99%
“…Most cell membranes are composed of phosphatidyl linkages (Han and Gross, 2004). The bond for the sn-2 fatty acid is always an ester bond (Pulfer and Murphy, 2003) and unsaturated fatty acids are preferred. Common notation for a molecular species follows the format x:y with x representing the number of carbons and y the number of double bonds.…”
Section: Introductionmentioning
confidence: 99%